2021
DOI: 10.3389/fpsyg.2021.705574
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of VR Avatar Embodiment on Improving Attitudes and Closeness Toward Immigrants

Abstract: Past research has discussed how the embodiment of an outgroup avatar in virtual reality (VR) can reduce intergroup bias. However, little is known about the mechanisms and boundary conditions that shape this effect. This study examines how the embodiment of both outgroup and ingroup VR avatars in different orders influences attitudes and perceived closeness toward a co-ethnic immigrant outgroup in Singapore. It also investigates the role of empathy and social identity orientation (SIO) in this relationship. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 77 publications
(131 reference statements)
1
23
0
Order By: Relevance
“…Banakou et al [ 73 ] also show that experiencing the world from the minority outgroup’s (i.e. Black people) perspective improves attitudes towards that group, and so do Peck et al [ 74 ], Salmanowitz [ 75 ], Christofi et al [ 76 ], Chen et al [ 77 , 78 ], Chowdhury et al [ 79 ], Tong et al [ 53 , 80 ], and Zhang et al [ 81 ]. However, other studies contest these findings by showing that intergroup contact experienced from the minority perspective does not necessarily have any effect on intergroup attitudes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Banakou et al [ 73 ] also show that experiencing the world from the minority outgroup’s (i.e. Black people) perspective improves attitudes towards that group, and so do Peck et al [ 74 ], Salmanowitz [ 75 ], Christofi et al [ 76 ], Chen et al [ 77 , 78 ], Chowdhury et al [ 79 ], Tong et al [ 53 , 80 ], and Zhang et al [ 81 ]. However, other studies contest these findings by showing that intergroup contact experienced from the minority perspective does not necessarily have any effect on intergroup attitudes.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is also evidence that both intergroup contact [ 56 , 72 ] and embodiment in an outgroup avatar [ 74 , 77 , 78 ] in VR can successfully be used to decrease racial bias. Furthermore, evidence by Hasler et al [ 56 ] and Hasson et al [ 48 ] suggests that the effect of VR contact is not specific for interracial attitudes, but can also improve in other, critical intergroup conflict situations: both studies showed that Jewish Israelis’ attitude towards Palestinians could be improved using VR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the scope of our questionnaires was limited to measure participants' subjective ratings of ownership, agency and appearance during the VR embodiment. There are indications 10.3389/fpsyg.2022.989582 Frontiers in Psychology 08 frontiersin.org that, at the individual level, traits (e.g., empathy or nervousness during the VR immersion) might contribute to enhance prejudice reduction in VR (Peck et al, 2013;Chen et al, 2021) and future studies might want to include questionnaires to evaluate participants also along those dimensions. Finally, future studies should explore whether the changes in the race IAT observed here using VR are also associated with changes in behavior.…”
Section: Discussionmentioning
confidence: 99%